Design of a visual guiding system for IAUV docking - Xinqian Bian; Xiaojuan Wang; Wei Zhang; Zheping Yan (2009 International Conference on Mechatronics and Automation, 2009)
IAUV (Intervention Autonomous Underwater Vehicle) is a main direction for AUV's future development. An important feature for IAUV is the capability of autonomous underwater docking. On this other hand, underwater vision in IAUV is gaining increasing attention nowadays. To achieve a high reliable, optimized docking system, a guiding system for docking based on the philosophy of visual dynamic positioning to line was put forward. Approaches of visual ranging and heading measurement were studied and their resolutions were analyzed. Based on this, a scheme for the guiding system's fundamental structure and guiding & control approach were defined attaching priority to the overall reliability. The fundamental hardware selection principles and results were also enclosed. This design course set a ground for further realization of a reliable correct docking system and could act as a reference for other underwater visual system design.